The kiss - Steel, Danielle (New York : Delacorte Press, 2001)
In this novel of compassion and courage, a solitary kiss changes lives forever when a man and a woman traveling together are involved in a horrific accident. It takes all their strength and courage to begin the long journey to recovery and heal the pain in their bodies as well as their spirits.
Keywords: Married people -- Fiction; Love stories